Some educational requirements to renew the religious discourse in the light of contemporary global transformations - Abo-kamoun, Mohamed Abdel Aati Salamah (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to clarify the educational requirements for the renewal of religious discourse in the light of the results of contemporary global transformations, by identifying the concept of innovation and its justifications and controls, and the most important contemporary global transformations that affect the identification of educational goals. The study concluded that the most important educational requirements, the development of creative and critical thinking skills, and the development of concepts Dialogue and coexistence with the other and employ educational technology.